Production of deuterons, tritons, 3He nuclei, and their antinuclei in pp collisions at √s=0.9, 2.76, and 7 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Beck, Hans; Borissov, Alexander; Danisch, Meike; Glässel, Peter; Kim, Jiyoung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; Ohlson, Alice; et al. (Physical review, 2018)
Invariant differential yields of deuterons and antideuterons in pp collisions at √s = 0.9, 2.76 and 7 TeV and the yields of tritons, 3He nuclei, and their antinuclei at √s = 7 TeV have been measured with the ALICE detector at the CERN Large Hadron Collider. The measurements cover a wide transverse momentum (pT) range in the rapidity interval |y|<0.5, extending both the energy and the pT reach of previous measurements up to 3 GeV/c for A=2 and 6 GeV/c for A=3. The coalescence parameters of (anti)deuterons and 3¯¯¯¯He nuclei exhibit an increasing trend with pT and are found to be compatible with measurements in pA collisions at low pT and lower energies. The integrated yields decrease by a factor of about 1000 for each increase of the mass number with one (anti)nucleon. Furthermore, the deuteron-to-proton ratio is reported as a function of the average charged particle multiplicity at different center-of-mass energies.